2019
DOI: 10.30605/ethicallingua.v6i1.1114
|View full text |Cite
|
Sign up to set email alerts
|

Omission: Common Simple Present Tense Errors in Students' Writing of Descriptive Text

Abstract: This research is aimed to determine and to describe the errors in using simple present tenses in writing descriptive texts made by students, especially in the class D of sixth semester of English Education Department at IAIN Palopo. The data were obtained by conducting a test and using a checklist. Then, the writing products were analyzed using Surface Strategy Taxonomy by Dulay (1982). The result of this research was presented descriptively. From the result, the omission errors were found as the highest of oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Amongst all of the mistakes, misformation is the most common error made by students (Siswoyo, 2016). In another similar study, omission errors have been found as the frequent errors made by students (Masruddin, 2019). From these studies, students are still struggling with present tense verb learning.…”
Section: Present Tense Verbsmentioning
confidence: 80%
“…Amongst all of the mistakes, misformation is the most common error made by students (Siswoyo, 2016). In another similar study, omission errors have been found as the frequent errors made by students (Masruddin, 2019). From these studies, students are still struggling with present tense verb learning.…”
Section: Present Tense Verbsmentioning
confidence: 80%
“…Therefore, the writer fulfilled the affixation process of attaching affixes to some words that can be used to make the derivational of affixation in Wawonii dialect. The result of the derivational of affixation might be seen at the According to Katamba (1993) a prefix is a morpheme which only occurs when attached to some other morpheme or morphemes such as a root or stem or base. There are four gathered in this study indicates the derivational affixes in Wawonii dialect, they are: prefix Man-, Me-, Pom-, Mong.…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, the derivational of prefixes in Wawonii language namely mon-, me-, pom-, mong, according to Katamba (1993) a prefix is a morpheme which only occurs when attached to some other morpheme or morphemes such as a root or stem or base. The prefixes of mon-, me-, pom-, and mong-, are derivational affixes which got form the word namely, monsupiri, meraha, mepayasa, pompekatae, mongkulati, and metabako.…”
Section: Discussionmentioning
confidence: 99%
“…Perlin, Sartika, and Nery (2020) stated that tense is a part of grammar that functions to describe the story that happened. Structure or grammar is one of the essential language components that students must learn (Masruddin, 2019). Tense is a grammatical expression of time relation between two events of time or situation.…”
Section: Introductionmentioning
confidence: 99%